2017
DOI: 10.2967/jnumed.116.187690
|View full text |Cite
|
Sign up to set email alerts
|

Functional Imaging Signature of Patients Presenting with Polycythemia/Paraganglioma Syndromes

Abstract: Pheochromocytoma/paraganglioma (PPGL) syndromes associated with polycythemia have previously been described in association with mutations in the von Hippel-Lindau gene. Recently, mutations in the prolyl hydroxylase gene (PHD) 1 and 2 and in the hypoxiainducible factor 2 a (HIF2A) were also found to be associated with multiple and recurrent PPGL. Such patients also presented with PPGL and polycythemia, and later on, some presented with duodenal somatostatinoma. In additional patients presenting with PPGL and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 34 publications
1
33
0
1
Order By: Relevance
“…The detection rates of 68 Ga-DOTA-SST PET and other imaging modalities ( 18 F-FDOPA PET, 18 F-FDG PET, and 123/131 I-MIBG scanning) are illustrated in Figure 3. 68 Ga-DOTA-SST PET consistently showed a higher detection rate than 18 F-FDOPA PET, 18 F-FDG PET, and 123/131 I-MIBG scintigraphy, with the exception of one study regarding polycythemia/paraganglioma syndrome (45). In that study, 68 Ga-DOTA-SST PET showed the lowest detection rate of 35% (95% confidence interval [CI], 24%-48%), whereas the detection rate for 18 F-FDOPA PET was 99% (95% CI, 93%-100%).…”
Section: Qualitative Synthesismentioning
confidence: 89%
See 4 more Smart Citations
“…The detection rates of 68 Ga-DOTA-SST PET and other imaging modalities ( 18 F-FDOPA PET, 18 F-FDG PET, and 123/131 I-MIBG scanning) are illustrated in Figure 3. 68 Ga-DOTA-SST PET consistently showed a higher detection rate than 18 F-FDOPA PET, 18 F-FDG PET, and 123/131 I-MIBG scintigraphy, with the exception of one study regarding polycythemia/paraganglioma syndrome (45). In that study, 68 Ga-DOTA-SST PET showed the lowest detection rate of 35% (95% confidence interval [CI], 24%-48%), whereas the detection rate for 18 F-FDOPA PET was 99% (95% CI, 93%-100%).…”
Section: Qualitative Synthesismentioning
confidence: 89%
“…Thus, 13 studies were included in the qualitative synthesis. We further excluded 4 studies that had exclusive patient populations: SDHB mutation (22), SDHx mutation in pediatric patients (24), sporadic type (23), and polycythemia/paraganglioma syndrome (45); inclusion of those studies might hinder generalization of the results. Therefore, 9 studies (215 patients) with no specific inclusion criteria for subtype were included in the metaanalysis (13)(14)(15)(16)(17)(18)(19)(20)(21), with the assumption that this pooled population might reflect patients with unknown genetic status in clinical practice.…”
Section: Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations